Medication persistence and discontinuation of rivaroxaban and dabigatran etexilate among patients with non-valvular atrial fibrillation. (3rd October 2015) - Nelson, Winnie W.; Song, Xue; Thomson, Erin; Smith, David M.; Coleman, Craig I.; Damaraju, C.V.; Schein, Jeffrey R.
Abstract: Objective: To compare real-world persistence and discontinuation among non-valvular atrial fibrillation (NVAF) patients on rivaroxaban and dabigatran in the US. Methods: A large nationally representative US claims database was used to conduct a retrospective cohort analysis of patients with NVAF on rivaroxaban or dabigatran between October 2010 and March 2013. The index date was the date of the first prescription of rivaroxaban or dabigatran. All patients had ≥6 months of data prior to the index date and were followed until the earliest of inpatient death, end of continuous enrollment, or end of the study period. Rivaroxaban patients were matched 1:1 with dabigatran patients using the propensity score matching technique. Cox proportional hazards models were employed to estimate the adjusted hazard ratios (aHRs) of non-persistence and discontinuation. Persistence was defined as absence of a refill gap of ≥60 days. Discontinuation was defined as no additional refill for at least 90 days and until the end of follow-up. Results: A total of 30, 337 NVAF patients on rivaroxaban or dabigatran met the study criteria. All 7259 rivaroxaban patients were matched 1:1 to dabigatran patients. Compared with dabigatran users, rivaroxaban patients were 11% less likely to become non-persistent with therapy (aHR: 0.89, 95% CI 0.84–0.95) and 29% less likely to discontinue therapy (aHR: 0.71, 95% CI 0.66–0.77). Limitations: Claims data are subject to miscoding and inaccuracies. Refill data may not fully reflect actual medication taken. Confounding may remain even after propensity score matching and additional adjustments in model. Longer follow-up may produce more precise estimates of persistence and discontinuation. Conclusions: This matched cohort analysis indicated that, compared to dabigatran, rivaroxaban was associated with better persistence and lower rates of discontinuation.